2018
DOI: 10.21082/ijas.v19n1.2018.p33-47
|View full text |Cite
|
Sign up to set email alerts
|

Soil Potassium Nutrient, Temperature and Rainfall Required to Generate ‘Honey Taste’ of Cilembu Sweet Potato

Abstract: <p>Indonesia produces normal and “honey taste sweet potatoes” (HTSP), but soil properties and climate factors that govern the unique honey taste and its sugar content have not yet comprehensively evaluated. The objective of the study was to assess and evaluate the soil nutrients and climate factors generating honey taste of Cilembu Rancing cultivar. Soils and plant tissues were sampled at different elevations for various macro- and micro-nutrient analyses and that tubers for sugar analysis. Results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 16 publications
3
9
0
1
Order By: Relevance
“…This has been reported by several researchers, where genetics significantly contribute to variations in sweet potato yields in different growing environments (Andrade et al 2016;Maulana et al 2022). In other studies, sweetness levels in sweet potatoes also showed significant differences in different locations (Anda et al 2018;Solihin et al 2018). This shows that the environment in which plants grow can affect the quality and chemical composition of the plants.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…This has been reported by several researchers, where genetics significantly contribute to variations in sweet potato yields in different growing environments (Andrade et al 2016;Maulana et al 2022). In other studies, sweetness levels in sweet potatoes also showed significant differences in different locations (Anda et al 2018;Solihin et al 2018). This shows that the environment in which plants grow can affect the quality and chemical composition of the plants.…”
Section: Introductionsupporting
confidence: 70%
“…This is because both environments have relatively high potassium (K) content (Sumedang dry field = 1.22 cmol kg -1 and Bandung dry field = 0.89 cmol kg -1 ). K content in the soil can affect the increase in sweetness levels in sweet potatoes (Anda et al 2018). The nutrient content in the Sumedang paddy field environment was relatively high, therefore it was only suitable for certain types or genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Tidak ditemukannya korelasi nyata pada kelerengan dan C-organik pada tanah diperkirakan juga disebabkan oleh faktor lainya seperti vegetasi, maupun faktor manusia berupa penggunaan lahan secara intensif (Rahmayanti et al, 2018). Menurut Anda et al (2018), kandungan Corganik pada tanah tidak bergantung pada perbedaan ketinggian tempat dan cenderung lebih tinggi pada daerah yang permukaannya lebih datar.…”
Section: Hubungan Kelerengan Dengan C-organikunclassified
“…Cilembu sweet potato is a sweet potato that specific in Cilembu village, the adjacent area to Cimanggung Sub District. It has a special sweet honey taste (Anda et al, 2018), and the sweetness quality fulfill the requirements of export standard (Agustina and Erwina, 2016). This sweet potato supplies market in several countries like Japan, Singapore, South Korea (Hoeridah and Sarianti, 2011).…”
Section: Introductionmentioning
confidence: 99%